Pemberdayaan Lansia melalui Kampung Ramah Lansia: Peningkatan Aspek Manajemen dan Sosial Kemasyarakatan di Argorejo, Sedayu - Nur Kholis; Okimustava; Dody Hartanto; Ulaya Ahdiani; Yusutria; Bambang Sudarsono; Nani Aprilia; Eko Susanto (Politeknik Piksi Ganesha Indonesia, 2026)
The Age‑Friendly Village program in Argorejo, Sedayu aims to enhance older adults’ managerial and socio‑communal capacities through non‑formal learning and community‑based participatory activities. The service used a one‑group pre–post participatory design with 30 older adults, accompanied by structured mentoring (preparation– socialization–implementation– evaluation- sustainment). The instrument was a Likert 1–5 questionnaire with two subscales: management (10 items) and socio‑communal (10 items). Data analysis comprised descriptive statistics (means & percentages), normality testing of difference scores, followed by paired t‑test or Wilcoxon (p<0.05) and effect sizes (Cohen’s d/r). Results showed significant gains: management increased from 2.76 (55.2%) to 4.14 (82.8%) (+27.6%), and the socio‑communal aspect rose from 2.72 (54.4%) to 4.26 (85.2%) (+30.8%). These findings confirm the effectiveness of a participatory approach in strengthening older adults’ autonomy, align with SDGs 3, 4, 10, and 11, and support IKU 2 and IKU 5. Replication with multi‑stakeholder support is recommended.